2021
DOI: 10.3390/jcm10020312
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Resting-State Functional Anticorrelation between Attention and Executive Control Networks in Schizotypal Personality Disorder

Abstract: Exploring the disruptions to intrinsic resting-state networks (RSNs) in schizophrenia-spectrum disorders yields a better understanding of the disease-specific pathophysiology. However, our knowledge of the neurobiological underpinnings of schizotypal personality disorders mostly relies on research on schizotypy or schizophrenia. This study aimed to investigate the RSN abnormalities of schizotypal personality disorder (SPD) and their clinical implications. Using resting-state data, the intra- and inter-network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The RSNs were defined using validated independent component analysis (ICA) templates from the HCP (Human Connectome Project), which had supported by empirical data [40,42,43]. We selected the 8 main RSNs were used as the networks of interest, including 32 ROIs representing DMN, FPN, SN, DAN, LN, VN, SMN, and CN.…”
Section: Roi-to-roi Whole Brain Functional Connectivity Analysismentioning
confidence: 99%
“…The RSNs were defined using validated independent component analysis (ICA) templates from the HCP (Human Connectome Project), which had supported by empirical data [40,42,43]. We selected the 8 main RSNs were used as the networks of interest, including 32 ROIs representing DMN, FPN, SN, DAN, LN, VN, SMN, and CN.…”
Section: Roi-to-roi Whole Brain Functional Connectivity Analysismentioning
confidence: 99%
“…51 Furthermore, some of the previous studies have found this relation, and argued that schizotypy may lead to schizophrenia and other spectrum disorders. 10,[52][53][54][55] As per the disconnection hypothesis, the observations of schizophrenia can be generalized to schizotypy. 56 This hypothesis asserts that schizophrenia can be conceived as the faulty interaction of functional systems, such as cortical areas and sub-areas, that are used for adaptive sensory-motor integration, perceptual synthesis, and cognition.…”
Section: Discussionmentioning
confidence: 99%